Partial Eruption of Solar Filaments. I. Configuration and Formation of Double-decker Filaments - Yijun Hou; Chuan Li; Ting Li; Jiangtao Su; Ye Qiu; Shuhong Yang; Liheng Yang; Leping Li; Yilin Guo; Zhengyong Hou; Qiao Song; Xianyong Bai; et al. (The Astrophysical Journal, 2023)
Partial eruptions of solar filaments are the typical representatives of solar eruptive behavior diversity. Here we investigate a typical filament partial eruption event and present integrated evidence for the configuration of the pre-eruption filament and its formation. The Chinese H α Solar Explorer H α observations reveal a structured Doppler velocity distribution within the pre-eruption filament, where distinct redshift only appeared in the eastern narrow part of the southern filament region and then disappeared after the partial eruption, while the northern part dominated by blueshift remained. Combining the Solar Dynamics Observatory and Advanced Space-based Solar Observatory observations, together with nonlinear-force-free-field modeling results, we verify that there were two independent material flow systems within the preflare filament, whose magnetic topology is a special double-decker configuration consisting of two magnetic flux ropes (MFRs) with opposite magnetic twist. During the formation of this filament system, continuous magnetic flux cancellation and footpoint motion were observed around its northern end. Therefore, we propose a new double-decker formation scenario: that the two MFRs composing such a double-decker configuration originated from two magnetic systems with different initial connections and opposite magnetic twist. Subsequent magnetic reconnection with the surrounding newly emerging fields resulted in the motion of the footpoint of the upper MFR to the region around the footpoint of the lower MFR, thus leading to the eventual formation of the double-decker configuration consisting of two MFRs with similar footpoints but opposite signs of magnetic twist. These results provide a potential way to determine unambiguously the progenitor configuration of a partially eruptive filament and reveal a special type of double-decker MFR configuration and a new double-decker formation scenario.